2009
DOI: 10.1186/1745-9974-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Cough in adult cystic fibrosis: diagnosis and response to fundoplication

Abstract: Background: Gastroesophageal reflux is one of the most common causes of chronic cough in the general population. Reflux occurs frequently in patients with cystic fibrosis (CF). We undertook laparoscopic Nissen fundoplication in adult CF patients with a clinical diagnosis of reflux cough who had failed conventional medical therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…A recent uncontrolled study by Fathi et al showed beneficial effects of Nissen fundoplication in a group of CF patients reducing both cough and exacerbation rate. 45 A limitation of this study is the small group of CF patients in which these examinations were executed. This was due to the fact that invasive studies like these are very often refused by the CF population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent uncontrolled study by Fathi et al showed beneficial effects of Nissen fundoplication in a group of CF patients reducing both cough and exacerbation rate. 45 A limitation of this study is the small group of CF patients in which these examinations were executed. This was due to the fact that invasive studies like these are very often refused by the CF population.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroesophageal reflux (GER) has been associated with chronic respiratory symptoms, such as cough and wheeze, and declining lung function in patients with cystic fibrosis (CF) 1–5. Furthermore, elimination of reflux through anti‐reflux surgery results in improvement in pulmonary symptoms thus proving that reflux can cause or exacerbate pulmonary disease 6–10. Early studies have hypothesized that the mechanism of lung injury by GER is either a vagally mediated response to acid in the distal esophagus or direct damage to the lung epithelium by acid.…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term use may adversely affect bone health in susceptible populations . Fundoplication has been reported to be beneficial in decreasing reflux‐cough sequence and respiratory exacerbations . Yet, morbidity of the procedure was high in a group of pediatric patients with CF .…”
Section: Luminal Diseasementioning
confidence: 99%
“…70 Fundoplication has been reported to be beneficial in decreasing reflux-cough sequence and respiratory exacerbations. 71 Yet, morbidity of the procedure was high in a group of pediatric patients with CF. 72 Fundoplication may therefore be reserved for high-risk patients such as the group of lung transplant candidates where it appears to decrease the postoperative decline in lung function parameters.…”
Section: Disorders Of Motilitymentioning
confidence: 99%